The first one, ten times as small and then the answer in parenthesis
Equation 1: x + y = 40 ; therefore y = 40 - x
Equation 2: 25x + 15y = 900
Find x first:
25x + 15 (40 - x) = 900
25x + 600 - 15x = 900
10x = 900 - 600
x = 300÷10
x = 30 hours Chris needs to spend for tutoring job
y = 40 - 30
y = 10 hours Chris needs to spend for referencing job
Answer:
![(f-g)(x) = 5^x +3x -2](https://tex.z-dn.net/?f=%28f-g%29%28x%29%20%3D%205%5Ex%20%2B3x%20-2)
Step-by-step explanation:
The value (f-g)(x) means subtract the function g from f. This can be done by combining only like terms between each.
![(f-g)(x) = 5^x - 4 -(-3x-2)\\(f-g)(x) = 5^x - 4 +3x + 2\\(f-g)(x) = 5^x +3x -2](https://tex.z-dn.net/?f=%28f-g%29%28x%29%20%3D%205%5Ex%20-%204%20-%28-3x-2%29%5C%5C%28f-g%29%28x%29%20%3D%205%5Ex%20-%204%20%2B3x%20%2B%202%5C%5C%28f-g%29%28x%29%20%3D%205%5Ex%20%2B3x%20-2)
Step-by-step explanation:
-2w=9+7
-2w=16
w=16/-2
w=-8